Problematika kompetensi pedagogi guru terhadap karakteristik peserta didik - Ilin Nurhamidah (Jurnal Teori dan Praksis Pembelajaran IPS, 2018)
In the process of education, teachers play an important role as a determinant of the achievement of educational goals. The learning process in the classroom is seen to play an important role when serving learners in learning. Pedagogic competence is the ability to manage the learning of learners which includes students' understanding, design and implementation of learning, evaluation of learning outcomes, and development of participants. Teachers will build a positive attitude in learning, generate curiosity, encourage independence and accuracy of intellectual logic, and create conditions for learning. Therefore, teachers are expected to be able to design activities, communication, and association that leads to learning. Interest, talent, ability, and potential learners will not develop optimally without the help of teachers. Learners one and the other there are basic characteristics, then the teacher must pay attention to individual characteristics of learners. Characteristics of students, ie (a) individuals possessing typical physical and psychical potentials, (b) developing individuals, (c) individuals requiring individual guidance and humane treatment, (d) the individual has the ability to be independent. The problems faced by the teacher about the lack or inability to master the characteristics of learners when implementing the learning, among others: (1) inability to master the characteristics of moral-emotional aspects of learners, (2) lack of mastery of socio-cultural aspects of learners, (3) lack of control (4) lack of mastering the intellectual aspect of the learner, (5) lack of mastering the moral aspect of the learner, (6) there is some kind of child character when learning. Efforts by teachers to integrate values and attitudes education in schools can be done using several approaches, according to Amri (2011: 89) are: (1) cul-tivation of values, (2) cognitive development, (3) self-clarification, (4) learning do.DOI: 10.17977/um022v3i12018p027